READING AS A WINDOW TO THE WORLD: EFFORTS TO REDUCE GADGET ADDICTION AND INCREASE INTEREST IN READING AMONG TEENS - Sirait, Grace Deo Valensia (JOURNAL OF SOCIAL, JUSTICE AND POLICY, 2025)
Teenagers are the age group most susceptible to device addiction in the current digital era, which affects their declining interest in reading and eroding literacy culture. Reading does, in fact, play a significant function as a window to the world that broadens knowledge, develops character, and opens insights. The purpose of this article is to look at how reading activities might be utilized as a substitute to lessen reliance on technology while rekindling teens' enthusiasm in reading. This study observes literacy practices in social and educational contexts using a descriptive qualitative method and a literature study methodology. According to the study's findings, creative and contextual approaches, such as providing bacaan materials that meet the needs of the students, encouraging group study sessions, using social media for educational purposes, and fostering relationships between friends and classmates, can be effective strategies for drawing attention away from less productive gadget use. As a result of viewing education as an activity that is enlightening, relevant, and integrated with the lives of the elderly, it is hoped that literature will once again become an important part of their lives, leading to the emergence of younger generations that are more adept at using technology and possess critical thinking skills.